Evaluation of the Rutting Performance of the Field Specimen Using the Hamburg Wheel-Tracking Test and Dynamic Modulus Test - Xiongwei Dai; Yanshun Jia; Shaoquan Wang; Ying Gao (Advances in Civil Engineering)
Rutting is a major distress occurring in the service life of the asphalt pavement, especially in hot weather areas. A laboratory-produced specimen is widely used for rutting performance evaluation which may not be completely represented by the field situation. The objective of this study is to evaluate the rutting performance of field specimens from the Chongqing highway by utilizing the Hamburg wheel-tracking test (HWTT) and dynamic modulus test. Different test conditions were conducted on the HWTT by investigation of the actual local weather condition. The results showed that rutting depth was different under different test conditions, and 10000 loading cycles were recommended as the maximum loading cycles. Particularly, several factors that influence the rutting depth were investigated, and the specimen height of 6 cm is more appropriate for the HWTT. Additionally, different test conditions were proposed as the HWTT test condition for different asphalt concrete (AC) layers in the Chongqing area. Rutting contribution of each AC layer to the pavement structure was analyzed. Moreover, the dynamic modulus at 54.4°C, 5 Hz and 54.4°C, 1 Hz could effectively represent the rutting performance of the asphalt mixture, and the dynamic modulus test is recommended for the rutting performance evaluation of the full-thickness AC layer.